Kinetics, thermodynamics, and physical characterization of corn stover (Zea mays) for solar biomass pyrolysis potential analysis. (July 2019) - Rony, Asif Hasan; Kong, Lingli; Lu, Wenyang; Dejam, Morteza; Adidharma, Hertanto; Gasem, Khaled A.M.; Zheng, Yuan; Norton, Urszula; Fan, Maohong
Graphical abstract: Highlights: Corn stover (CS) was analyzed by TGA, SEM, and elemental analyzer. Solar pyrolysis product of CS was analyzed using GC–MS, GPC, SEM. Kinetics of CS pyrolysis was determined using KAS, FWO, and CR method. Thermodynamic parameters were determined for CS pyrolysis. Abstract: Solar pyrolysis of agricultural waste has huge potential for sustainable production of fuel and chemical feedstock. In this paper, the kinetics, thermodynamics, and physical characterization of corn stover (CS) collected from Wyoming, USA was conducted with respect to solar pyrolysis. The kinetics and thermodynamics of the CS pyrolysis was analyzed in detail using the methods described by KAS (Kissinger-Akahira-Sunose) and FWO (Flynn-Wall-Ozawa), from which the activation energy, Gibbs energy, Arrhenius pre-exponential factor, enthalpy, and entropy were derived.14 other kinetics models based on reaction order, diffusion, nucleation, geometric contraction, power models were also examined, and models based on diffusion was found to be best suited. The CS was used for solar pyrolysis of biomass and the products were analyzed by mass spectroscopy, ICP-MS, GPC, micro-GC, and Elemental analyzer. The results show that CS is suitable for solar pyrolysis to produce chemicals and other fuels.